Effects of sodium-glucose cotransporter-2 inhibitors use in asia towards cardiorenal outcomes: Updated systematic review and meta-analysis - Fonny Cokro, Rani Sauriasari, Dicky Levenus Tahapary,, and Heri Setiawan, (Journal of Applied Pharmaceutical Science, 2024)
Effective diabetes prevention and control are needed to address Asia’s growing diabetes epidemic. This meta-analysis assessed how sodium-glucose cotransporter-2 inhibitors (SGLT2Is) affected cardiorenal outcomes in Asians. A comprehensive review of literature from PubMed, EMBASE, CENTRAL, and citation searching up to December 2023 identified 13 randomized controlled trials comparing SGLT2Is and placebo, involving 14,922 Asians with type 2 diabetes and a history of atherosclerotic cardiovascular disease risk, heart failure (HF), or chronic kidney disease. The RoB 2 tool assessed bias, while RevMan 5.3 synthesized quantitative data. There was no significant reduction in major adverse cardiovascular events for Asians (HR = 0.82, 95%CI = 0.66–1.01) or in the Asia region (HR = 0.88, 95%CI = 0.76–1.01). However, a notable benefit was observed for the composite of cardiovascular death/worsening HF in Asians (HR = 0.64, 95% CI = 0.52–0.80) and the Asia region (HR = 0.66, 95%CI = 0.58–0.75). Additionally, SGLT2Is demonstrated favourable renal outcomes for Asians (HR = 0.64, 95% CI = 0.51–0.80) and the Asia region (HR = 0.64, 95%CI = 0.56–0.74). Safety assessments revealed 2.88 times increased risk of Genital Mycotic Infections. GRADE analysis showed moderate to high certainty for all primary outcomes. In conclusion, SGLT2Is improve Asian renal outcomes. Real-world studies in Asia are recommended to assess the practical cardiorenal efficacy of SGLT2Is in routine healthcare settings.
Keywords: Asia, Asian, cardiovascular diseases, meta-analysis, renal insufficiency, chronic, sodium-glucose transporter 2 inhibitors